Using migrating growth strata to confirm a ∼230-km-long detachment thrust in the southern Tarim Basin. (January 2022) - Chen, Hanlin; Zhang, Yuqing; Cheng, Xiaogan; Lin, Xiubin; Deng, Hongdan; Shi, Xuhua; Li, Yong; Wu, Hongxiang; Li, Chunyang; Yang, Shaomei
Abstract: The amount of fault slip and timing of fault activation are two fundamental elements of quantitatively structural analysis. Currently, these two parameters are mainly determined by the geometry of fault-related folds and the growth strata over the fault ramp. In this study, we propose a new type of growth strata that directly constrain both the amount of fault slip and the timing of fault activity at the fault flat based on interpretations of seismic reflection profiles and related numerical modeling of the Manan Structure along the southern Tarim Basin. The seismic sections show a rootless synform beyond the north limb of the Manan Anticline with the hinge dipping toward north. Numerical modeling suggests that this synform is a result of northward migration of the growth strata along with the slip of the underlying detachment thrust with a bulge at the fault surface. We define this type of growth strata 'migrating growth strata (MGS)' . The dipping direction of the hinge of the synform marks the slip direction, the projecting distance of the hinge on the fault surface measures the slip amount, and the timing of the MGS represent the timing of the activity of the underlying detachment thrust. Analyses of the Manan MGS along the southern Tarim Basin suggest ∼13–22 km of northward fault slip passed by the Manan Structure along the basal Cenozoic detachment and was finally absorbed by the Mazatagh Belt, which confirms a ∼230-km-long detachment thrust along the southern Tarim Basin and provide key evidence to establish a kinematic linkage between the Hotan and Mazatagh Belts. Two-segment style of the hinge of the synform indicates that the Manan Structure has undergone two-stage evolution related to the lower Cambrian and the basal Cenozoic detachments, respectively. These results imply that detachments in difference depths and their sequential activities are key in transmitting strain from the Tibetan Plateau into the Eurasian continental interiors. Highlights: Seismic sections show a rootless synform in Manan Structure, southern Tarim Basin. The synform was produced by growth strata migrating with the detachment thrust. Such a structure was defined as 'migrating growth strata (MGS)'. MGS provide a new tool for quantitatively analyzing the fold-thrust belts. The results demonstrate a ∼230-km-long detachment thrust in southern Tarim Basin.